Determinants of the Participation of Long-Term Contraceptive Method Users on Fertiled Aged Couples at Kampung KB Kelurahan Rengas Pulau Medan Marelan in 2018 - Tampubolon, Emelia A.; Hidayat, Wisnu; Tarigan, Frida Lina (Sari Mutiara Indonesia University Press, 2018)
The increase in population in Indonesia has caused population problems in which people use Non-MKJP (Non-Long Term Contraceptive Method), compared with MKJP. The negative impact of low coverage of MKJP users is the increase in population which brings about low provision in manpower. The objective of the research was to find out some factors which influenced of MKJP users’ participation in PUS (productive-aged couples) at Kampung KB, Kelurahan Rengas Pulau, Medan Marelan, in 2018. The research used observational analytic method with cross sectional dresign. The population was 365 KB (Family Planning) acceptors at Kampung KB, Kelurahan Rengas Pulau, and 78 of them were used as the samples. The result of multiple logistic regression analysis at p-value=0.25 showed that there was the influence of knowledge (p=0.018, PR=5.987), parity (p=0.001, PR=0.058), husbands’ or families’ support (p=0.001, PR=21.061), culture (p=0.005, PR=0.041), the distance of health facility (p=0.010, PR=0.089) on MKJP users’ participation in PUS. However, there was no influence of health care providers (p=0.054, PR=4.507) on MKJP users’ participation in PUS. The variable which had the most dominant influence of husbands’ or families’ support which had the opportunity of 21.061 time more than that of the other variables in MKJP users’ participation in PUS. It is recommended that the health care providers support the use of MKJP so that PUS can understand the benefit of using contraception.